Group cognitive behavioural therapy with virtual reality exposure versus group cognitive behavioural therapy with in vivo exposure for social anxiety disorder and agoraphobia: a protocol for a randomised clinical trial. Issue 2 (2nd February 2022) - Arnfred, Benjamin; Bang, Peter; Hjorthøj, Carsten; Christensen, Clas Winding; Stengaard Moeller, Kirsten; Hvenegaard, Morten; Agerskov, Lone; Krog Gausboel, Ulrik; Soe, Ditte; Wiborg, Peter; Smith, Christopher Ian Schøler; Rosenberg, Nicole; et al.
Abstract : Introduction: Anxiety disorders have a high lifetime prevalence, early-onset and long duration or chronicity. Exposure therapy is considered one of the most effective elements in cognitive behavioural therapy (CBT) for anxiety, but in vivo exposure can be challenging to access and control, and is sometimes rejected by patients because they consider it too aversive. Virtual reality allows flexible and controlled exposure to challenging situations in an immersive and protected environment. Aim: The SoREAL-trial aims to investigate the effect of group cognitive behavioural therapy ( CBT-in vivo ) versus group CBT with virtual reality exposure ( CBT-in virtuo ) for patients diagnosed with social anxiety disorder and/or agoraphobia, in mixed groups. Methods and analysis: The design is an investigator-initiated randomised, assessor-blinded, parallel-group and superiority-designed clinical trial. Three hundred two patients diagnosed with social anxiety disorder and/or agoraphobia will be included from the regional mental health centres of Copenhagen and North Sealand and the Northern Region of Denmark. All patients will be offered a manual-based 14-week cognitive behavioural group treatment programme, including eight sessions with exposure therapy. Therapy groups will be centrally randomised with concealed allocation sequence to either CBT-in virtuo or CBT-in vivo . Patients will be assessed at baseline, post-treatment and 1-year follow-up by treatment blinded researchers and research assistants. The primary outcome will be diagnosis-specific symptoms measured with the Liebowitz Social Anxiety Scale for patients with social anxiety disorder and the Mobility Inventory for Agoraphobia for patients with agoraphobia. Secondary outcome measures will include depression symptoms, social functioning and patient satisfaction. Exploratory outcomes will be substance and alcohol use, working alliance and quality of life. Ethics and dissemination: The trial has been approved by the research ethics committee in the Capital Region of Denmark. All results, positive, negative as well as inconclusive, will be published as quickly as possible and still in concordance with Danish law on the protection of confidentially and personal information. Results will be presented at national and international scientific conferences. The trial has obtained approval by the Regional Ethics Committee of Zealand (H-6-2013-015) and the Danish Data Protection Agency (RHP-2014-009-02670). The trial is registered at ClinicalTrial.gov as NCT03845101 . The patients will receive information on the trial both verbally and in written form. Written informed consent will be obtained from each patient before inclusion in the trial. The consent form will be scanned and stored in the database system and the physical copy will be destroyed. It is emphasised that participation in the trial is voluntary and that the patient can withdraw his or her consent at any time without consequences for further and continued treatment. Trial registration number: NCT03845101 .